Pelanggaran Prinsip Kerja sama dalam Debat Pemilihan Umum Calon Presiden 2019 - Sofiana, Sofiana; Hermaliza, Hermaliza (UIR PRESS, 2021)
Violation is an act or case of violating applicable rules or regulations. Speakers and speech partners in communicating must comply with the principle of cooperation, but in the 2019 Presidential Candidate General Election debate the author found speeches that violated the principle of cooperation. This is what makes the author interested in conducting this research entitled